A reappraisal of Joseph Brennan and the achievements of Irish banking and currency policy 1922–1943. (22nd April 2021) - Drea, Eoin; Barry, Frank
Abstract : Joseph Brennan, as secretary of the Irish Department of Finance (1923–7) and chair of the Irish Currency Commission (1927–43), was a pivotal influence on Irish banking and currency affairs. Yet, within the existing literature, his adherence to conservative British norms is seen as providing a 'bleak prescription' for the Irish economy. However, such a view ignores the fact that Brennan was far from dogmatic on banking and currency issues and underplays his incrementalist, and often internationalist, approach to the development of Irish monetary institutions. Brennan's actions up to the early 1940s were based on the realities of Ireland's slowly receding economic and intellectual dependency on Britain, a 'dependency' often misrepresented in the existing literature as a more primitive, pre-Keynesian, conservative approach. However, rather than acting as a restraining influence on Irish economic development, the policies Brennan advocated enabled Ireland to avoid the instability associated with many smaller, emerging nation states in the 1920s and 1930s. The focus on continuity – which guaranteed currency and banking stability – represented the realities of Ireland's reliance on the sluggish British economy in the decades after independence. Brennan's achievement, in helping to sustain banking and currency stability notwithstanding economic uncertainty, a fragile political environment (and suspicious banking interests), deserves wider acknowledgement.